Unattended Home Labor until Complete Cervical Dilatation Ending with Hospital Delivery: Analysis of 238 Pregnancies - Ozlem Gun Eryilmaz; Nasuh Utku Dogan; Cavidan Gulerman; Leyla Mollamahmutoglu; Nedim Cicek; Ruya Deveer (Obstetrics and Gynecology International)
Objectives. Hospital fear and avoidance of the routine hospital obstetrical interventions cause some women with low-risk pregnancies to spend most of the active labor period at home, and subsequently they present to the hospital for delivery. Our aim was to analyze the maternal and neonatal outcomes of pregnancies with a planned hospital birth, yet spending the first stage of labor at home without a health provider and completing the delivery in the hospital setting. Methods. We retrospectively compared 238 pregnancies having home labor plus hospital delivery (study group) with 476 pregnancies that had spent the whole labor in the hospital setting, considering various maternal and neonatal outcomes. Results. Cesarean and episiotomy rates were lower (P<0.0001 and P<0.001, resp.), but neonatal intensive care unit admissions of the infants were more prevalent (P<0.01) in the study group. Other maternal and neonatal outcomes including neonatal mortality were comparable. Conclusion. Although our preliminary data generally do support the safety of home active labor plus hospital delivery for low-risk pregnancies, the clinical implications of current data warrant further prospective trials.